Effects of prior cold working on low cycle fatigue behavior of stainless steels, titanium alloy Timetal 834 and superalloy in 718: A review - Singh V. (My University, 2025)
This paper gives a brief review of the efforts made to study the effects of cold rolling on low cycle fatigue (LCF) behavior of stainless steels, titanium alloy Timetal 834 and Ni-Fe based Super alloy IN 718 at different temperatures and different strain amplitudes. Low Cycle Fatigue tests on cold worked 316L stainless steel at various temperatures from room temperature to 923K have been reported. In all tests the effect of 20% prior cold work(PCW) on LCF behavior of type 316L (N) stainless steel had been studied at 873K under total axial strain controlled mode in air at strain amplitudes from ±0.25% to ±1.0%. Fatigue life in the solution annealed condition was similar to that of the PCW material at higher strain amplitudes (≥0.5%) while at lower strain amplitudes the PCW material exhibited longer life. The influence of PCW on LCF behavior of type 304 and AISI 304LN stainless steel was studied at various temperatures and it was observed that the fatigue life was strongly dependent on prior cold work, temperature, and strain amplitude employed. Cold rolling of the titanium alloy Timetal 834 and age hardenable Ni-Fe-based superalloy IN 718 has been found to cause marked enhancement in LCF life at low strain amplitude and eliminate the bilinearity from the Coffin-Manson(C-M) relationship. Work carried on this aspect,however is very limited particularly in the case of Titanium alloys and Ni-Fe based Superalloy IN 718 © 2010 TIIM, India.